Influence of communication, discipline and work motivation on PT Vesinter Indonesia employee performance - Dian Tono; Inda Sukati (Institute of Computer Science (IOCS), 2024)
These days, there is more rivalry among businesses. They strive to outdo each other in terms of human resource development in order to grow their respective industries. Good employee performance may assist employers in reaching a certain degree of job effectiveness in fostering better working relationships with their workforce. There may be intense rivalry among enterprises as a result of the growth of company development in diverse service sectors. Naturally, every business has a unique plan in place to deliver a creative and inventive performance. This study sought to determine how PT Vesinter Indonesia employees' performance was impacted by communication, discipline, and work motivation. In the sample, 115 people responded. Quantitative study using a Likert scale is employed. The t test results show that, when it comes to the performance of PT Vesinter Indonesia employees, discipline has a significant effect with at value of 7.737> 1.98157 and a significant value of 0.001 < 0.05, communication has a significant effect with at value of 4.288 > t table 1.98157 and a significant value of 0.001 < 0.05, and motivation has not an insignificant effect with at value of 1.324> 1.98157 and a significant value of 0.188 < 0.05. Furthermore, the results of the f test show that, at a significance level of 0.001 <0.05, employees' performance at PT Vesinter Indonesia is strongly impacted by communication, discipline, and motivation. The f count is 134.451> f table 2.698398.